Einige Bemerkungen zu einer Arbeit von I. Kowalenko - Gnedenko, B.; Freier, B. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. В. Гнеденко, Б. Фрайер. Несколько замечаний к одной работе И. Н. Коваленко B. Gnedenka, B. Frajeris. Keletas pastabų apie vieną I. Kovalenkos darbą